A lightweight deep learning with feature weighting for activity recognition. (12th December 2022) - Ige, Ayokunle Olalekan; Mohd Noor, Mohd Halim
Abstract: With the development of deep learning, numerous models have been proposed for human activity recognition to achieve state‐of‐the‐art recognition on wearable sensor data. Despite the improved accuracy achieved by previous deep learning models, activity recognition remains a challenge. This challenge is often attributed to the complexity of some specific activity patterns. Existing deep learning models proposed to address this have often recorded high overall recognition accuracy, while low recall and precision are often recorded on some individual activities due to the complexity of their patterns. Some existing models that have focused on tackling these issues are always bulky and complex. Since most embedded systems have resource constraints in terms of their processor, memory and battery capacity, it is paramount to propose efficient lightweight activity recognition models that require limited resources consumption, and still capable of achieving state‐of‐the‐art recognition of activities, with high individual recall and precision. This research proposes a high performance, low footprint deep learning model with a squeeze and excitation block to address this challenge. The squeeze and excitation block consist of a global average‐pooling layer and two fully connected layers, which were placed to extract the flattened features in the model, with best‐fit reduction ratios in the squeeze and excitation block. The squeeze and excitation block served as channel‐wise attention, which adjusted the weight of each channel to build more robust representations, which enabled our network to become more responsive to essential features while suppressing less important ones. By using the best‐fit reduction ratio in the squeeze and excitation block, the parameters of the fully connected layer were reduced, which helped the model increase responsiveness to essential features. Experiments on three publicly available datasets (PAMAP2, WISDM, and UCI‐HAR) showed that the proposed model outperformed existing state‐of‐the‐art with fewer parameters and increased the recall and precision of some individual activities compared to the baseline, and the existing models.